2008
DOI: 10.1111/j.1365-2494.2007.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stem density of tropical swards and age of grazing cattle on their foraging behaviour

Abstract: The effects of stem density of tropical swards and age of cattle on their foraging behaviour were evaluated using artificial microswards, consisting of leaves of 20 cm in height and high tensile-resisting stems of 25 cm in height of Panicum maximum. The treatments consisted of a factorial combination of four stem densities of swards (0, 100, 200 and 400 stems m )2 ) and two ages of cattle (1-and 3-year-old steers). There was a significant interaction between stem density of sward and age of cattle for bite are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
2
33
0
11
Order By: Relevance
“…Thus, a significant increase in the mass of the residual forage between the third and fourth grazing cycles of the RP30 treatment was observed, thereby revealing the damage that was caused by stems in the use of forage. Benvenutti, Gordon and Poppi (2008) observed that with increasing stem densities, there is a restriction in the bite size and a consequent reduction in the instantaneous intake by 1 and 3-year-old steers.…”
Section: Anjos a J Dos Et Almentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, a significant increase in the mass of the residual forage between the third and fourth grazing cycles of the RP30 treatment was observed, thereby revealing the damage that was caused by stems in the use of forage. Benvenutti, Gordon and Poppi (2008) observed that with increasing stem densities, there is a restriction in the bite size and a consequent reduction in the instantaneous intake by 1 and 3-year-old steers.…”
Section: Anjos a J Dos Et Almentioning
confidence: 95%
“…This finding confirms the hypothesis that the increase in forage mass in response to the grazing interval is primarily a result of the increased stem biomass (Alexandrino et al, 2005). A high proportion of stem and dead forage in the forage mass hinders the forage apprehension capacity and hence the grazing efficiency, thereby decreasing the voluntary intake of grazing animals (Difante et al, 2011;Benvenutti et al, 2008;Brancio et al, 2003).…”
Section: Anjos a J Dos Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased participation of leaf blade of forage sorghum in the total forage mass reflects the preferential consumption of leaves by the animals when compared to other plant parts (FONSECA et al, 2013) due to the lower bromatological quality of the stems in relation to leaves (BENVENUTTI et al, 2008). As the cycle advances and the photoperiod decreases, the plants tend to flower differentiation, decreasing the leaf appearance rate, which is lower compared to the consumption of leaves, reflecting the decrease in mass and leaf supply.…”
Section: Resultsmentioning
confidence: 99%
“…BURNS et al (1989) destacam que, sob pastejo, as massas de forragem e folha verde podem alterar o desempenho individual dos animais e a taxa de crescimento do pasto. Em pastos artifi ciais de Panicum maximum, o comportamento seletivo de pastejo de bovinos variou de acordo com a resistência à preensão dos colmos (BENVENUTTI et al, 2008). Estudos mostram que, em pastagens de capimtanzânia sob pastejo contínuo, durante a estação do inverno, a altura do pasto pode alterar características do pasto (CANTO et al, 2001) e, em consequência, o desempenho de novilhos de corte (CANTO et al, 2002).…”
Section: Introductionunclassified